2020
DOI: 10.1111/dth.13767
|View full text |Cite
|
Sign up to set email alerts
|

Global coronavirus pandemic ( SARS‐CoV ‐2): Past , present , and future of pediatric dermatology

Abstract: Two months have passed since the World Health Organization (WHO) declared the pandemic of the Coronavirus Disease 19 (COVID-19), caused by the SARS-CoV-2 virus, on 11 March 2020. Medical and healthcare workers have continued to be on the frontline to defeat this disease, however, continual changes are being made to their working habits which are proving to be difficult. Although the skin is not the main target of the SARS-CoV-2 infection, it is strongly involved both directly and indirectly, in many aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In conclusion, despite the encouraging experience of our centre and other centres around the world, the relative weight of hydroxychloroquine in the treatment or prevention of COVID‐19 disease, either alone or in association with macrolides, has not be established yet 22,23 . Recent studies also highlight the misleading nature of anecdotal experiences reported when contrasted with the controlled clinical trials.…”
Section: Variables N = 50mentioning
confidence: 87%
“…In conclusion, despite the encouraging experience of our centre and other centres around the world, the relative weight of hydroxychloroquine in the treatment or prevention of COVID‐19 disease, either alone or in association with macrolides, has not be established yet 22,23 . Recent studies also highlight the misleading nature of anecdotal experiences reported when contrasted with the controlled clinical trials.…”
Section: Variables N = 50mentioning
confidence: 87%